2003
DOI: 10.1183/09031936.03.00039803
|View full text |Cite
|
Sign up to set email alerts
|

Lower risk of atopic disorders in whole cell pertussis-vaccinated children

Abstract: This study addressed whether whole cell pertussis-vaccinated children have a different risk of atopic disorders compared with children who did not receive this vaccination.Data on vaccination status, atopic disorders and child and family characteristics of the children of 700 families were collected in this retrospective study. A minority of these 700 families refused vaccinations for religious reasons. The relation between pertussis-vaccination status and atopic disorders was analysed by means of adjusted log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…In contrast, authors of a Dutch retrospective study reported pertussis vaccination to be associated with lower risk of eczema in 6-year-old children. 17 In this study, 39 of 44 infants classified as not vaccinated for pertussis had no vaccination at all, and pertussis-vaccinated infants were also DPT vaccinated. Therefore, the comparison made in this study would seem to reflect DPPT-vaccinated children versus completely unvaccinated children.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, authors of a Dutch retrospective study reported pertussis vaccination to be associated with lower risk of eczema in 6-year-old children. 17 In this study, 39 of 44 infants classified as not vaccinated for pertussis had no vaccination at all, and pertussis-vaccinated infants were also DPT vaccinated. Therefore, the comparison made in this study would seem to reflect DPPT-vaccinated children versus completely unvaccinated children.…”
Section: Discussionmentioning
confidence: 99%
“…An IgE response to vaccine antigens is commonly detectable in the sera of children vaccinated with diphtheria/tetanus, and the IgE response to vaccine antigens is more pronounced among atopic individuals. 3,4 The epidemiologic evidence linking diphtheria, pertussis, tetanus (DPT) immunizations to childhood asthma or atopy is mixed, with studies showing an increased [4][5][6][7][8][9] or decreased risk [10][11][12] of developing asthma, or no association. [13][14][15][16][17][18][19] These studies have primarily addressed the question of whether asthma is more likely to develop in vaccinated versus unvaccinated children.…”
mentioning
confidence: 99%
“…Three of these were cross-sectional and thus could not account for temporal relationships between exposures and outcome. [25][26][27] Similarly to ours, 1 study was based on data from a population-based cohort with well separated assessment of vaccinations and health outcomes. 24 In this study pertussis vaccination was associated with lower prevalence of early atopic dermatitis and allergic sensitization.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…[7][8][9][10][11] Other studies, including a randomized clinical trial, 12,13 found no or only inconclusive evidence for an association, [14][15][16][17][18][19][20][21][22][23] and some reported that vaccination against pertussis may protect from atopy. [24][25][26][27] These differences are partly because of the biases affecting this type of research. Reliable vaccination data are often difficult to obtain and many studies have therefore relied on parental or personal recall.…”
mentioning
confidence: 96%